The endemic deer Haploidoceros mediterraneus (Bonifay) (Cervidae, Mammalia) from the Late Pleistocene of Cova del Rinoceront (Iberian Peninsula): origin, ecomorphology, and paleobiology. (15th March 2020) - Croitor, Roman; Sanz, Montserrat; Daura, Joan
ABSTRACT: This article reports the findings from a morphological and demographic analysis of the craniodental remains of the endemic continental deer Haploidoceros mediterraneus from the Late Pleistocene (MIS 5) of the Cova del Rinoceront (Castelldefels, Barcelona, Iberian Peninsula), the most complete assemblage of this species recorded in Europe. The presence of vestigial distal antler palmation and a posterior crown tine suggests that the genus Haploidoceros belongs to the Arvernoceros-Rucervus phylogenetic stock. The direct phyletic relationship between Haploidoceros mediterraneus and the ' Cervus elaphoides ' from the Early Pleistocene of Venta Micena is confirmed by the dental morphology and the shape of the proximal portions of the antlers. The article discusses the evolution of the typical morphological features of H. mediterraneus : including its protruding tube-shaped orbits; relatively large cheek teeth; and, narrow, pointed premaxillary bones. The demographic structure of the cervid remains (a predominance of juvenile and prime adult males) suggests a seasonal mortality peak for young males expelled from the optimal habitat during autumn and winter.